2006
DOI: 10.1108/09604520610711927
|View full text |Cite
|
Sign up to set email alerts
|

Linking a service‐driven market orientation to service quality

Abstract: PurposeThe purpose of this research is to empirically develop a service‐driven market orientation construct and test its relationships with service quality.Design/methodology/approachThe researcher employs Critical Incident Technique to generate items for the survey instrument. Then, the quantitative‐based descriptive research uses structured questionnaires to capture the perceptions of 558 university students from Malaysia which are used to understand the nature of the customer‐perceived market orientation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 62 publications
(75 reference statements)
3
74
0
4
Order By: Relevance
“…For instance, Voon's (2006) study found that perceived service quality in higher education had a greater impact on customer satisfaction and loyalty than maintaining a service market orientation by the higher educational institution. However, majority of the studies both in Nigeria and developed countries have focused on the relationship between students' satisfaction and demographic factors such as age, sex, marital status, year of study and nationality (Soutar & McNeil, 1996;Umbach & Porter, 2002;Perry, Sekelsy, & Skarsten, 2003;Tessema, Ready, & Malone, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Voon's (2006) study found that perceived service quality in higher education had a greater impact on customer satisfaction and loyalty than maintaining a service market orientation by the higher educational institution. However, majority of the studies both in Nigeria and developed countries have focused on the relationship between students' satisfaction and demographic factors such as age, sex, marital status, year of study and nationality (Soutar & McNeil, 1996;Umbach & Porter, 2002;Perry, Sekelsy, & Skarsten, 2003;Tessema, Ready, & Malone, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Students' satisfaction has been identified to have a significant impact on maintaining students' loyalty and retention (Cronin & Taylor, 1992;Voon, 2006;Brunson, 2010). For instance, Voon's (2006) study found that perceived service quality in higher education had a greater impact on customer satisfaction and loyalty than maintaining a service market orientation by the higher educational institution.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, experience in hospitality services has been regarded as a competitive tool as well as a way to gain superior service performance (e.g. [11], [12], [13], [14], [4]). However, there should be greater emphasis on empirical research of investigating the social and environmental aspects of customer experience for the priority service sector such as homestay tourism.…”
Section: Tourist Experience For Sustainable Homestaysmentioning
confidence: 99%
“…The qualitative (i.e., Focus Groups) and quantitative process (Structural Equation Modeling with AMOS) of developing the measurement cum management tool were scientifically done to develop the marketing construct (e.g. [2], [3], [4], [5]). …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, all the SERVMO components are found to be impactful on customer-perceived service quality, with the employee orientation being the most dominant factor. (Voon, 2006) Oliver (1980) empirically demonstrated that attitude was a superordinate concept of satisfaction. Cronin and Taylor (1992) investigated the path between satisfaction and service quality using a sample of eight service firms from four service sectors.…”
mentioning
confidence: 99%